2019
DOI: 10.1088/1757-899x/669/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Green Cimahi watershed for balancing water supply and flood control

Abstract: Lack and damage of clean water and also flooding occurred in Cimahi river basin. Water sources polluted by industry and human activities. The purpose of this study was to design the water balance model of the Cimahi watershed as a Green Watershed. The study locations were the Cimahi river, Cilember river, Cibeureum river and Cisangkan river, which flow through the city of Cimahi. The method used is the analysis of the rainfall runoff model with the hydrograph of convolution method in the four watersheds, land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Land use changes due to population growth have caused the condition of water availability in the Cimahi sub-watershed to be low or even shortage, especially from surface water. This condition is exacerbated by the occurrence of a dry season with little or no rainfall for aproximately six months [8]. In addition, pollution from the domestic, agricultural, and industrial sectors causes the water quality of the Cimahi river to be in a heavily polluted condition.…”
Section: Resultsmentioning
confidence: 99%
“…Land use changes due to population growth have caused the condition of water availability in the Cimahi sub-watershed to be low or even shortage, especially from surface water. This condition is exacerbated by the occurrence of a dry season with little or no rainfall for aproximately six months [8]. In addition, pollution from the domestic, agricultural, and industrial sectors causes the water quality of the Cimahi river to be in a heavily polluted condition.…”
Section: Resultsmentioning
confidence: 99%
“…Load discharges are calculated based on design rainfall that is multiplied convolutive (Equation 2) after being converted into effective rainfall [12], [13]. Design rainfall is calculated using Gumbel frequency analysis while effective rainfall is calculated using a runoff coefficient derived from the land use map.…”
Section: B Flood Risk Quantification Analysis Modelmentioning
confidence: 99%
“…It has been suggested that a study be conducted to integrate spatial planning processes through multidisciplinary institutions and cross-border administration (Asdak, Supian, & Subiyanto, 2018). Furthermore, there is a need for watershed management to balance water availability and needs, land cover and groundwater, and quality of surface water and groundwater (Safarina, Karnisah, Permana, & Sufianto, 2019). It is also possible to reduce local floods through natural and/or artificial water infiltration methods.…”
Section: Introductionmentioning
confidence: 99%